Prediction of Potential Regret in Marriage Conflict: Reviewed from Qur'anic Psychology and Family Therapy - Fithri Choirunnisa Siregar; Esli Zuraidah Siregar (Bulletin of Counseling and Psychotherapy, 2026)
Marriage in Islam is highly encouraged as an act of worship to Allah SWT and as the fulfillment of the Sunnah of the Prophet Muhammad ﷺ. As a lifelong commitment, marriage can be a source of happiness as well as prolonged psychological stress due to inevitable marital conflicts. Although many conflicts are minor and resolvable, they often lead to regret when handled unwisely. Such regret may reflect a genuine desire to preserve the sanctity of marriage, yet it can become destructive when emotional immaturity prevents healthy conflict resolution. This study adopts a qualitative conceptual approach by integrating two perspectives: Qur’anic Psychology as an Islamic framework for understanding marital psychological dynamics, and Applied Psychology through Family Therapy as a practical strategy for managing marital conflict. The findings indicate that marital regret can serve as a constructive signal when approached through Qur’anic psychological principles, encouraging self-awareness, emotional regulation, and spiritual reflection. Family Therapy complements this perspective by offering structured techniques that promote effective communication, emotional maturity, and mutual understanding between spouses.The integration of Qur’anic Psychology and Family Therapy highlights that marital conflict is not merely a relational issue but a divine test that requires both spiritual consciousness and psychological skills. Constructive conflict resolution grounded in Islamic values and supported by applied psychological methods can strengthen marital harmony and sustain the sacred bond of marriage.